THE CURRENT ROLE OF BUKHARA ENLIGHTENMENT IN MODERN TIMES - Navfal Ashurov (Web of Journals Publishing, 2024)
The article highlights the main ideas of the late nineteenth and early twentieth centuries in the socio-philosophical views of our people related to the Enlightenment and its new stage, Jadidism. The spiritual heritage of the Bukhara enlighteners has been philosophically analyzed.
Keywords: Jadid, enlightenment, tolerance, philosophy.